Informativeness of Self-Reports of ADHD Symptoms in Monitoring Response to Stimulant Treatment in Clinically Referred Adults With ADHD. Issue 3 (February 2020) - Biederman, Joseph; Fitzgerald, Maura; Spencer, Thomas J.; Adler, Lenard A.; Abrams, Jessica; Biederman, Itai; Faraone, Stephen V.
Objective: To investigate the informativeness of self-reports of ADHD symptoms in adults with ADHD in the clinical setting.Method: Subjects were clinically referred adults aged 19 years to 67 years of age of both sexes ( N = 54). All subjects were on stable doses of stimulant and were considered responders to treatment. ADHD symptoms were assessed using the ADHD Investigator Symptom Rating Scale (AISRS) and the ADHD Self-Report Scale (ASRS). Spearman's rank correlations were used to assess the correlations between clinician-assessed ADHD and patients' self-reports.Results: Spearman's rank correlation analysis found evidence of a strong, positive association between total scores on the AISRS and the ASRS ( r s = .65, df = 52, p < .001).Conclusion: Results have important implications for the management and monitoring of treatment response in the clinical setting through patients' self-report.